Opportunities and challenges for doing business in vietnam via a multi factor model impacts - DAT, PHAM MINH; HUY, DINH TRAN NGOC (The journal of contemporary issues in business and government, 2021)
Currently, FDI inflows in Vietnam has been increasing, during impacts from Covid 19 and China-US commerce war which facilitates opportunities for US and Chinese firms to enter Vietnam market to attract qualified labor sources at competitive salary. From this fact, it is the time for us to consider to evaluate impacts from multi factors on Doing Business score (DB score) in the country.Authors use both qualitative, analytical and synthesis methods, combined with OLS regression method. Research results show us that in a 4 factor model, Export and FDI registration and export have positive correlation with DB score, while CPI and Import have negative correlation with DB score. Next, we recognize that CPI and FDI registration have higher coefficient and impact on DB score. Therefore, The authors propose recommendations for improving DB score in Vietnam from ex- import and FDI attracting policies. The model can be expanded and applied to other emerging markets.